Navigating occupational safety and health challenges in sustainable infrastructure projects: a comprehensive review - Baghdadi, Ahmad (Frontiers in Built Environment, 2024)
Ensuring occupational safety and health (OSH) is paramount in infrastructure projects due to their inherently high-risk nature and the increased likelihood of accidents. Despite its importance, numerous obstacles impede the successful adoption of OSH measures in these settings. Addressing these challenges is key to not only implementing OSH protocols effectively but also to improving working conditions and managing other operational facets like quality and environmental concerns, ultimately resulting in better infrastructure developments. Adopting proactive OSH strategies is crucial for preventing significant accidents and fostering a safety culture within infrastructure projects. This review focuses on identifying the primary obstacles and barriers to effective OSH in infrastructure projects, laying the groundwork for improving safety performance in the sector. It highlights organizational and legislative issues as the foremost challenges due to their direct impact on safety culture, resource distribution, compliance, and accountability. Although factors related to environmental and safety practices are deemed less critical, they are nonetheless vital for comprehensive risk management and the promotion of a safe working environment. Tackling these issues is imperative for cultivating a strong safety culture and safeguarding the health of workers on infrastructure projects. It is also essential to acknowledge the distinct OSH challenges presented by different construction scenarios to devise customized safety measures and effectively reduce risks. This review emphasizes the necessity of recognizing the unique aspects of each construction project, addressing specific dangers, and meeting regulatory demands to achieve thorough safety management.